Three new bee species of Rhophitulus Ducke (Hymenoptera, Apidae, Protandrenini) from Argentina and Brazil - Ramos, Kelli S. (Zootaxa, 2014)
This work describes three newly discovered species of Rhophitulus Ducke, 1907: R. labiosus n. sp. from Minas Gerais (Brazil), R. mimus n. sp. from Salta (Argentina), and R. xenopalpus n. sp. from Catamarca and Tucumán (Argentina). Photographs of the holotype of Rhophitulus steinbachi (Friese, 1916) are provided, and modifications in the morphology of a female of R. xenopalpus n. sp. when parasitized by Strepsiptera are recorded for the first time for the genus.